Comparison of determinants of morbidities of late preterms and terms - Kaur, Gagandeep; Chhabra, Gurpreet Singh; Thapar, Karuna (International Journal of Contemporary Pediatrics, 2020)
Background: To compare the determinants of neonatal morbidity in late preterms and terms. Methods: A total of 100 live late preterm (34-0/7 to 36-6/7 weeks) and 100 term infants (37-0/7 to 41-6/7 weeks) admitted in sri guru ram das institute of medical sciences and research were randomly selected to participate in this case control study. The study group include 100 neonates within gestation age of 34 0/7 to 36 6/7 weeks. Equal number of terms between 37 0/7 to 41-6/7 gestation age was taken for comparison. The maternal history including both antenatal and natal history as well as new-born profile was taken. Results: Maternal risk factors have been found to be the major determinants of morbidity in late preterms with PROM (p<0.0001), sepsis and hypertension being significant contributors. Respiratory distress, neonatal jaundice, sepsis has been found to be major morbidity factors in late preterms. The average duration of admission was higher in late preterms than terms. Conclusions: Late preterm infants have higher risks for acute metabolic complications, mortality and long-term disabilities as compared to term infants. Morbidities like respiratory distress, neonatal jaundice, sepsis, hypoglycaemia and hypothermia are more in late preterms due to their immaturity. The risks associated with late preterm birth suggest the need for refinement of obstetric paradigms to extend pregnancy duration if benefits outweigh risk to fetus and mother. There is need to make obstetricians and families aware of complications pertaining to late preterm birth and improving surveillance of high-risk pregnancies.